The Influence of Service Quality and Satisfaction on Interest in Return Visits of Inpatient Patients at Bekasi Regency Hospital - Sutra Gustianingrum; MGS Aritonang; Nurita Andayani (Publikasi Indonesia, 2024)
This success can be achieved if it provides quality services that have an impact on patient satisfaction and will further affect the interest in re-visiting. This study aims to determine the effect of service quality on patient satisfaction and the influence of both on re-visitation interest. This research was conducted using a quantitative descriptive method. The study sample was taken using a purposive sampling technique of 100 respondents. Data were collected through questionnaires, and analysis using SEM (Structural Equation Model). The results showed that good service quality has a positive and significant effect on patient satisfaction, creating a satisfying experience and building trust. Patient satisfaction, as a result of adequate service quality, also has a positive and significant impact on repeat visit intention.